The Effect of Graphic Design Integration in Augmented Reality Learning Media on Junior High School Students’ Conceptual Understanding - Angga Reza, Yolandita (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Augmented Reality (AR) has emerged as an effective educational tool for visualizing abstract concepts and increasing student engagement through interactive digital content. This study aims to examine the impact of integrating pedagogical graphic design principles into the development of AR-based learning media for junior high school science subjects. Using a mixed-methods approach, the research involved the design, implementation, and evaluation of an AR prototype comprising three modules: the solar system, human anatomy, and basic chemical reactions. Each module was designed using pedagogically informed visual strategies such as color coding, 3D modeling, and intuitive interactivity to support conceptual understanding. The study adopted a quasi-experimental design involving pretest and posttest procedures with 60 junior high school students, divided into two groups: an experimental group (AR with optimized graphic design) and a control group (standard AR). Sample selection criteria included students in grades 7 and 8 with basic access to digital devices. Data were analyzed using an independent sample t-test to compare conceptual understanding improvements between the groups. Results indicated a statistically significant increase in the experimental group (27.8%) compared to the control group (12.3%), with a significance level of p < 0.01. In addition to cognitive gains, observational and interview data revealed strong emotional engagement, longer interaction times, and higher learning motivation among students in the experimental group. These findings highlight the crucial role of pedagogical graphic design in enhancing both cognitive and affective outcomes of AR-based learning. The study recommends the development of accessible, teacher-friendly AR platforms equipped with modular visual design libraries to facilitate broader implementation in educational environments.